Menanamkan Nilai-nilai Hardiness pada Anak Usia Dini melalui Storytelling - Handayani, Ratna Mustika; Martani, Wisjnu (Universitas Muhammadiyah Metro, 2024)
Someone hardworking will be able to adapt to various challenging situations. They have self-control and commitment to achieve their goals. Therefore, the values of hardiness need to be instilled in children’s early childhood to make them grow up to be individuals with high fighting spirits and be able to face difficulties and unpleasant situations. This study aims to determine the effect of storytelling on the development of hardiness traits in early childhood children. This research used an untreated control group design with dependent pretest and post-test samples. The study participants were 20 children between 5 and 6 years old. They were divided into control and experimental groups, consisting of consistent. The research used 12 colored pictures sized 21cm-14.5cm as the instruments. Those instruments were arranged based on aspects and indicators of hardiness. Data analysis used Anava mixed design, showing that storytelling could form hardiness. Children in the experimental group had a higher understanding of hardiness than children in the control group. Based on the result, the researcher suggests parents and teachers consistently instill complex values in early childhood children through storytelling.